Vertigo as a Predominant Manifestation of Neurosarcoidosis - Tasnim F. Imran; Sobia Nizami; Igor Eyzner; Neena Mirani; Tanzib Hossain; Robert Fede; Eugenio Capitle (Case Reports in Medicine)
Sarcoidosis is a granulomatous disease of unknown etiology that affects multiple organ systems. Neurological manifestations of sarcoidosis are less common and can include cranial neuropathies and intracranial lesions. We report the case of a 21-year-old man who presented with vertigo and uveitis. Extensive workup including brain imaging revealed enhancing focal lesions. A lacrimal gland biopsy confirmed the diagnosis of sarcoidosis. The patient was initially treated with prednisone, which did not adequately control his symptoms, and then was switched to methotrexate with moderate symptomatic improvement. Our patient had an atypical presentation with vertigo as the predominant manifestation of sarcoidosis. Patients with neurosarcoidosis typically present with systemic involvement of sarcoidosis followed by neurologic involvement. Vertigo is rarely reported as an initial manifestation. This case highlights the importance of consideration of neurosarcoidosis as an entity even in patients that may not have a typical presentation or systemic involvement of disease.